ASSESSMENT OF PERCEPTION OF CHINA IN THE KAZAKHSTANI SOCIETY: MYTHS AND REALITY - OSHAKBAYEV, Rakhim; ZHAKYPOVA, Fatima; ISSAYEV, Bolat; KOLESNIK, Xeniya (CENTRAL ASIA AND THE CAUCASUS, 2021)
The article examines the image of China in Kazakhstani society, analyzes the perception and attitude of Kazakhstan’s population towards China. Based on the results of a survey of Kazakhstan’s population (N = 2,594) and an expert survey (N = 23), the authors identify the principal stereotypes about China in the mass perception of Kazakhstanis. Also, the authors assess the level of awareness of the population about China and its projects and the perception by the Kazakhstani people of the economic, political and socio-cultural influence of Kazakhstan’s eastern neighbor. In addition, the article examines the attitude of Kazakhstanis to bilateral cooperation be- tween Kazakhstan and China and the manifestations of Sinophobia in Kazakhstani society and identi